Constructing Third Space In A Multi-Religious Society: Interreligious Relations In Kalimantan Tengah, Indonesia - Iqbal, Asep; Erawati, Desi; Qodir, Abdul; Anwar, Khairil (KALAM, 2018)
A growing body of literature has given shape and voice to the emerging field of interreligious studies. However, most of related studies have tended to focus on the relations between religious communities in Western countries. The scholars have not given adequately attention to the richness and complexity of the relations among different religious communities in Asian region and possibility of theoretical and practical contributions to interreligious relations. This article seeks to analyzes the interreligious relations among different religious communities in Indonesia based on data generated through interviews with Muslim, Christian and Kaharingan communities in Indonesia. Employing the concept of Third Space, this article focuses on the performance of interreligious relations between Muslims, Christians, and the adherents of local religion of Kaharingan in Kalimantan Tengah province, Indonesia. It explains the the third space issue in the narrative of interfaith relations and the third space in the practice of interreligious relations in the region. This study find that the diverse religious communities in Indonesia practice a peaceful and co-existence life, which is strongly inspired and driven by shared particular social-cultural contexts of rich treasures and precious tradition of cultural heritage in the forms of Indonesian communalism and community spirit. It concludes that the diverse religious communities create “third spaces”, as common grounds between them which are shared at individual, institutional and societal levels.